Antibiotic resistance characteristics of potential probiotic Lactobacillus strains - Dang, Huong Thu; Dinh, Huy Son; Loc, Tu Anh; Nguyen, La Anh (Vietnam Journal of Science and Technology, 2023)
Antibiotic-resistant bacteria are increasingly common and threaten human health. Recently, antibiotic resistance in food associated bacteria become an emerging threat to this state. These bacteria may act as reservoirs of antibiotic resistance genes and transfer to commensal or pathogenic bacteria in the human intestines. Therefore, either probiotics or starter cultures have to be evaluated for antibiotic interaction. In this study, the antibiotic susceptibility of seven Lactobacillus strains was determined. The MIC values revealed that all strains were resistant to tetracycline, ciprofloxacin, vancomycin and aminoglycoside antibiotics group (gentamicin, neomycin, kanamycin and streptomycin). However, the results from PCR analysis showed that parC gene for ciprofloxacin resistance was only present in Lb. fermentum SMC2; vanX gene, responsible for the vancomycin resistance, was found in two strains Lb. plantarum AS34 and TJ26. Most strains showed susceptibilityto at least one type of protein synthesis inhibit antibiotics: chloramphenicol, erythromycin and clindamycin. Four strains Lb. brevis NCTH24, Lb. casei PK2, Lb. fermentum SBV2, and Lb. plantarum NCDC3 did not carry any antibiotic resistance genes which indicates these antibiotic resistances are intrinsic and nontransmissible.